2010
DOI: 10.1007/s00103-010-1134-8
|View full text |Cite
|
Sign up to set email alerts
|

Früherkennungsuntersuchungen als Instrument im Kinderschutz

Abstract: Routine well-child visits, implemented as a means of secondary prevention and covered by health insurance, lead to early identification of disorders and abnormalities in child development."Guiding principles for children" (by the G-BA) have determined the content of the eleven examinations, ranging from U1 immediately after birth to J1 in adolescence; eight of them take place within the first four years of age. Since cases of child maltreatment, neglect, or abuse became public in 2007, almost all German federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…The increased utilization of early detection examinations and also the reduction of social differences in participation rates can be linked to various measures. Since 2007, new invitation, reminder and feedback systems were introduced in all federal states, even though the regulations vary from one federal state to the other [ 13 , 14 ]. In Brandenburg, for example, in cooperation with the ‘Bündnis Gesund Aufwachsen’, a registration system for the U6 to U8 was established in 2008 that commits doctors to confirm to a newly introduced central body, when the corresponding examinations have taken place.…”
Section: Resultsmentioning
confidence: 99%
“…The increased utilization of early detection examinations and also the reduction of social differences in participation rates can be linked to various measures. Since 2007, new invitation, reminder and feedback systems were introduced in all federal states, even though the regulations vary from one federal state to the other [ 13 , 14 ]. In Brandenburg, for example, in cooperation with the ‘Bündnis Gesund Aufwachsen’, a registration system for the U6 to U8 was established in 2008 that commits doctors to confirm to a newly introduced central body, when the corresponding examinations have taken place.…”
Section: Resultsmentioning
confidence: 99%
“…Early Child Health Checkups starting with the birth of the child have long been the main national prevention strategy to preserve child well-being. However, parents' participation in these early child health checkups has not become compulsory yet (Hock et al, 2012) and advocacy to expand their scope to the identification of child physical and sexual abuse has yet remained unsuccessful (Thaiss et al, 2010). But recent tragic events of child maltreatment forced a change in national maltreatment prevention initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of ASHIP data has shown that 12-year-old girls have a 7 times higher probability of having received at least one HPV vaccine dose if they attended the J1 health checkup [118]. The introduction of a compulsory invitation and response procedure for the J1 health check-up could be helpful: in the Rhineland-Palatinate, this procedure has increased attendance at the J1 health check-up by 25% [119]. The routine well-child check-up 'U11' (9-10 years of age) is another option for offering the vaccination, but not all SHI funds cover this screening examination, so it is not offered consistently in Germany.…”
Section: Implementation Of a General Hpv Vaccinationmentioning
confidence: 99%